Molecular mechanism of diaminomaleonitrile to diaminofumaronitrile photoisomerization: an intermediate step in the prebiotic formation of purine nucleobases - Szabla, Rafał; Góra, Robert W; Sponer, Jiří; Sponer, Judit E (Chemistry (Weinheim an der Bergstrasse, Germany), 2014)
The photoinduced isomerization of diaminomaleonitrile (DAMN) to diaminofumaronitrile (DAFN) was suggested to play a key role in the prebiotically plausible formation of purine nucleobases and nucleotides. In this work we analyze two competitive photoisomerization mechanisms on the basis of state-of-the-art quantum-chemical calculations. Even though it was suggested that this process might occur on the triplet potential-energy surface, our results indicate that the singlet reaction channel should not be disregarded either. In fact, the peaked topography of the S1 /S0 conical intersection suggests that the deexcitation should most likely occur on a sub-picosecond timescale and the singlet photoisomerization mechanism might effectively compete even with a very efficient intersystem crossing. Such a scenario is further supported by the relatively small spin-orbit coupling of the S1 and T2 states in the Franck-Condon region, which does not indicate a very effective triplet bypass for this photoreaction. Therefore, we conclude that the triplet reaction channel in DAMN might not be as prominent as was previously thought.
Keywords: fumaráty; prebiotika; nukleotidy; Quantum Theory; puriny; Prebiotics; nucleobases; Models, Molecular; Nucleotides; molekulární modely; quantum chemistry; Photochemistry; nitrily; Nitriles; Purines; nucleotides; fotochemie; photochemistry; kvantová teorie; Fumarates; isomerization